Rancang Bangun Aplikasi Pencatatan Stok dan Penjualan UD Pawon Kue - Trisno, Indra Budi; Chandra, Wiria (Universitas Nusantara PGRI Kediri, 2018)
Pawon Kue is a small home industry which sells various cake and rice box products. Pawon Kue was using books for recording orders and product selling. The method was used since the company established. However, the company experienced difficulities when using this method. The process to find how much the profit they got in a day was not easy, it also needed long time to find certain information, and there were big probability they could lose the recording books. Because of them, the author and the team developed a web based application for helping them in recording sales and stock listing. The team used waterfall model in software enginering model and used Unified Modeling Language in design and system analyst stage. After the testing stage, the research team found the application could help the owners for listing stock and product easier than before.